Spinal cord protection in open and endovascular aortic surgery: current strategies, controversies and future directions - Torre, Debora Emanuela; Pirri, Carmelo (Frontiers in Cardiovascular Medicine, 2025)
Spinal cord injury (SCI) remains one of the most devastating complications following open and endovascular thoracoabdominal aortic repair, significantly affecting both survival and quality of life. Despite considerable progress in surgical and endovascular techniques, effective perioperative strategies for SCI prevention continue to evolve. This review provides a comprehensive and critical appraisal of current knowledge on the pathophysiology of spinal cord injury, along with established and emerging protective interventions. Techniques such as cerebrospinal fluid drainage, distal aortic perfusion, staged repair, permissive hypertension and intraoperative neuromonitoring are examined in light of the latest clinical evidence. The role of anatomical and hemodynamic factors, as well as pharmacological adjuncts and experimental approaches, is discussed in detail. Persistent knowledge gaps and areas of controversy, particularly regarding the optimal timing and combination of protective strategies, are identified. Future perspectives are also outlined, emphasizing the need for personalized, physiology guided approaches based on patient specific risk profiles.